2010
DOI: 10.4049/jimmunol.0903271
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Contributes to Angiogenesis in Rheumatoid Arthritis

Abstract: Angiogenesis is an early and a critical event in the pathogenesis of rheumatoid arthritis (RA). Neovascularization is dependent on endothelial cell activation, migration and proliferation, and inhibition of angiogenesis may provide a novel therapeutic approach in RA. In this study, we document a novel role of IL-17 in mediating angiogenesis. Local expression of IL-17 in mouse ankles increases vascularity. We further demonstrate that IL-17 is angiogenic by showing its ability to promote blood vessel growth in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 165 publications
(153 citation statements)
references
References 52 publications
5
148
0
Order By: Relevance
“…Therefore, IL-17A/F uses PI3K signaling pathway to stimulate the migration of vascular endothelial cells, as is the same as IL-17A (Pickens et al 2010). Similar finding has been reported that the PI3K signaling plays an important role in VEGF-A-mediated migration of endothelial cells (Hayashi et al 2009).…”
Section: Dsupporting
confidence: 73%
See 1 more Smart Citation
“…Therefore, IL-17A/F uses PI3K signaling pathway to stimulate the migration of vascular endothelial cells, as is the same as IL-17A (Pickens et al 2010). Similar finding has been reported that the PI3K signaling plays an important role in VEGF-A-mediated migration of endothelial cells (Hayashi et al 2009).…”
Section: Dsupporting
confidence: 73%
“…express IL-17RA and IL-17RC on the cell surface (Moseley et al 2003;Pickens et al 2010;Fujie et al 2012). Thus, we examined the biological effects of IL-17A/F on in vitro angiogenesis-related functions of HMVECs.…”
Section: Effects Of Il-17a/f On the Growth Of Vascular Endothelial Cellsmentioning
confidence: 99%
“…IL-17A and IL-17F, which are the main members of the IL-17 family, have the greatest homology (20) and share the same receptor and regulatory elements (21). IL-17A and IL-17F have been reported to be involved in vascular regeneration in some diseases (11,12,16,(22)(23)(24). In our study, we found that neutralization of IL-17A led to reduced vascularity in the lung of OVA-challenged mice, whereas IL-17F antagonism did not markedly influence the microvascular regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The total perimeter of completely enclosed tubes in one field was calculated by Image-Pro Plus5.1, and the average of the total perimeter measurements was used for quantification. In addition, node formation (defined as a nodular contact formation of at least three adherent endothelial cell tubes) in five randomly selected microscopic fields (3100 magnification) was evaluated blindly (11,15).…”
Section: Tube Formation Assaymentioning
confidence: 99%
See 1 more Smart Citation